Efficiency of methionine and cystine utilization by broiler chickens using stable isotopes - Pacheco, Letícia G.; Sakomura, Nilva K.; Suzuki, Rafael M.; Dorigam, Juliano C. P.; Viana, Gabriel S.; Leme, Bruno B. (Wiley, 2020)
The aim of this study was to develop a method to determine the efficiency of utilization of Met and Cys using stable isotopes in order to reduce the number of sacrificed animals relative to the comparative slaughter technique. Met and Cys efficiencies were obtained separately and as total SAA values. Twenty-one 14- to 28-day-old broiler chickens were fed experimental diets containing different Met:Cys ratios (44:56, 50:50 and 56:44). Birds were given diets with daily supplements of L-(15N) Met (60 mmol/kg) or L-(15N2) Cys (35 mmol/kg) throughout the entire experimental period. Excreta were collected daily, and birds were euthanized at the end of the trial to collect feather-free bodies and feathers. Samples were analysed for 15N and 15N-Met content. The utilization efficiency for Met, Cys and Met + Cys for feather-free bodies was 55%, 75%, and 60%, while the efficiencies for feathers were estimated at 96%, 77% and 84% respectively.
Keywords: efficiency of amino acid utilization; stable isotopes; sulphur amino acids